Cognitive behavioral therapy for treatment-resistant depression: A systematic review and meta-analysis. (October 2018) - Li, Jia-Mei; Zhang, Yi; Su, Wen-Jun; Liu, Lin-Lin; Gong, Hong; Peng, Wei; Jiang, Chun-Lei
Highlights: Meta-analysis of CBT for patients with treatment-resistant depression. CBT has superior efficacy in patients with treatment-resistant depression. CBT take effect immediately after intervention and the effect can last for a long time. Abstract: Cognitive behavioral therapy (CBT) is a common psychotherapy characterized as treating mental diseases, such as depression. Though multiple studies have reported its effect in treatment-resistant depression, no qualified meta-analysis has ever assessed this effect before. In this study, we evaluated the efficacy of CBT for treatment-resistant depression patients and its continuous effect. We comprehensively searched PubMed, Embase, and Cochrane Library from inception to February 2018 for eligible randomized controlled trials (RCTs). A total of six RCTs involving 847 participants were included. Pooled analysis indicated that CBT was an efficient invention in reducing depression symptoms. Besides, CBT was also superior to control group in increasing response and remission rates. These effects could take effect at post-treatment, and last for 6 months, or even 1 year long. No publication bias was detected. These findings suggested that compared with routine antidepressant treatment, CBT has greater potential in taking immediate effect and has better mid-term and long-term prognosis.